Metabolic Adaptation, a Specialized Leaf Organ Structure and Vascular Responses to Diurnal N2 Fixation by Nostoc azollae Sustain the Astonishing Productivity of Azolla Ferns without Nitrogen Fertilizer - Brouwer, Paul; Bräutigam, Andrea; Buijs, Valerie A.; Tazelaar, Anne O. E.; van der Werf, Adrie; Schlüter, Urte; Reichart, Gert-Jan; Bolger, Anthony; Usadel, Björn; Weber, Andreas P. M.; Schluepmann, Henriette (Frontiers in Plant Science, 2017)
Sustainable agriculture demands reduced input of man-made nitrogen (N) fertilizer, yet N2 fixation limits the productivity of crops with heterotrophic diazotrophic bacterial symbionts. We investigated floating ferns from the genus Azolla that host phototrophic diazotrophic Nostoc azollae in leaf pockets and belong to the fastest growing plants. Experimental production reported here demonstrated N-fertilizer independent production of nitrogen-rich biomass with an annual yield potential per ha of 1200 kg-1 N fixed and 35 t dry biomass. 15N2 fixation peaked at noon, reaching 0.4 mg N g-1 dry weight h-1. Azolla ferns therefore merit consideration as protein crops in spite of the fact that little is known about the fern’s physiology to enable domestication. To gain an understanding of their nitrogen physiology, analyses of fern diel transcript profiles under differing nitrogen fertilizer regimes were combined with microscopic observations. Results established that the ferns adapted to the phototrophic N2-fixing symbionts N. azollae by 1) adjusting metabolically to nightly absence of N supply using responses ancestral to ferns and seed plants; 2) developing a specialized xylem-rich vasculature surrounding the leaf pocket organ; 3) responding to N-supply by controlling transcripts of genes mediating nutrient transport, allocation and vasculature development. Unlike other non-seed plants, the Azolla fern clock is shown to contain both the morning and evening loops; the evening loop is known to control rhythmic gene expression in the vasculature of seed plants and therefore may have evolved along with the vasculature in the ancestor of ferns and seed plants.